From component technology to integrated resource management: Evolution toward trandisciplinary research in a project in Ethiopia - Jabbar, M.A.; Mohamed-Saleem, M.A.; Li Pun, H.H. (SNSF, 2000)
The paper first discusses the need for moving from disciplinary to transdisciplinary research in addressing problems of human Development and environmental management. Then the experience of a research project in highland Ethiopia that started with disciplinary research and component technologies to address problems of poverty, malnutrition, low agricultural productivity and resource degradation and gradually moved towards integrated resource management and a transdisciplinary approach is described. Although a systems approach was adopted in the beginning to diagnose problems, initially discipline based component technology research was a dominant characteristics of the project. Individual technologies were designed and tested on-farm with farmer participation often separately, and their impacts were assessed mostly in bio-economic terms e.g. yield and income. Gradually the need for simultaneously assessing the economic, social and environmental effects of several technology interventions at plot, household and watershed/community levels were recognised. The research methods have been accordingly modified to adopt an integrated and holistic approach incorporating biophysical, economic and social dimensions of the ecosystem. Currently agroecosystem health approach to ecosystem analysis is being used as an integrative analytical framework. This evolution also meant a gradual shift from disciplinary to multidisciplinary to transdisciplinary approach to research.